Understanding the impact of Nagarik App on behavioural intention of the citizens of Kathmandu for the transition towards e-governance – An extended UTAUT study - Ghimire, Sagar; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
This study focuses on the residents of Kathmandu District in Nepal to understand the factors that strengthen and weaken their behavioural intention to use e-government services with the Nagarik App (a mobile application launched by the Government of Nepal in 2021) serving as a reference point for experience, a moderator. In the current digital era with increasing cyber threats alongside digital literacy, understanding the impact of trust and experience is vital. Using a quantitative descriptive research design, data from 490 respondents was collected online and analyzed with PLS-SEM to understand the impact of the four UTAUT constructs and trust on the behavioural intention. The results highlighted the significant role of facilitating conditions, effort expectancy and trust expectancy while also showing strong impact of experience as a moderator in some relationships. By emphasizing the role of trust, the study covers contemporary concerns of Kathmandu residents on the usage of digital government platforms and how Nagarik App has reshaped public perception of e-governance.